Toward adaptive radiotherapy for head and neck patients: Feasibility study on using CT‐to‐CBCT deformable registration for "dose of the day" calculations. Issue 3 (19th February 2014) - Veiga, Catarina; McClelland, Jamie; Moinuddin, Syed; Lourenço, Ana; Ricketts, Kate; Annkah, James; Modat, Marc; Ourselin, Sébastien; D'Souza, Derek; Royle, Gary
Abstract : Purpose: : The aim of this study was to evaluate the appropriateness of using computed tomography (CT) to cone‐beam CT (CBCT) deformable image registration (DIR) for the application of calculating the "dose of the day" received by a head and neck patient. Methods: : NiftyReg is an open‐source registration package implemented in our institution. The affine registration uses a Block Matching‐based approach, while the deformable registration is a GPU implementation of the popular B‐spline Free Form Deformation algorithm. Two independent tests were performed to assess the suitability of our registrations methodology for "dose of the day" calculations in a deformed CT. A geometric evaluation was performed to assess the ability of the DIR method to map identical structures between the CT and CBCT datasets. Features delineated in the planning CT were warped and compared with features manually drawn on the CBCT. The authors computed the dice similarity coefficient (DSC), distance transformation, and centre of mass distance between features. A dosimetric evaluation was performed to evaluate the clinical significance of the registrations errors in the application proposed and to identify the limitations of the approximations used. Dose calculations for the same intensity‐modulated radiation therapy plan on the deformed CT and replan CT were compared. Dose distributions were compared in terms of dose differences (DD), gamma analysis, target coverage, and dose volume histograms (DVHs). Doses calculated in a rigidly aligned CT and directly in an extended CBCT were also evaluated. Results: : A mean value of 0.850 in DSC was achieved in overlap between manually delineated and warped features, with the distance between surfaces being less than 2 mm on over 90% of the pixels. Deformable registration was clearly superior to rigid registration in mapping identical structures between the two datasets. The dose recalculated in the deformed CT is a good match to the dose calculated on a replan CT. The DD is smaller than 2% of the prescribed dose on 90% of the bodyˈs voxels and it passes a 2% and 2 mm gamma‐test on over 95% of the voxels. Target coverage similarity was assessed in terms of the 95%‐isodose volumes. A mean value of 0.962 was obtained for the DSC, while the distance between surfaces is less than 2 mm in 95.4% of the pixels. The method proposed provided adequate dose estimation, closer to the gold standard than the other two approaches. Differences in DVH curves were mainly due to differences in the OARs definition (manual vs warped) and not due to differences in dose estimation (dose calculated in replan CT vs dose calculated in deformed CT). Conclusions: : Deforming a planning CT to match a daily CBCT provides the tools needed for the calculation of the "dose of the day" without the need to acquire a new CT. The initial clinical application of our method will be weekly offline calculations of the "dose of the day, " and use this information to inform adaptive radiotherapy (ART). The work here presented is a first step into a full implementation of a "dose‐driven" online ART.